2019
DOI: 10.1063/1.5094166
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and challenges of high-pressure methods applied to thermoelectric materials

Abstract: We describe the current state of experimental studies of the effects of applied high pressure or stress on the thermoelectric properties and performance parameters of thermoelectric materials, as well as the challenges faced in this area and possible directions for future work. We summarize and analyze literature data on the effects of high pressure on the Seebeck coefficient (thermoelectric power) of different materials that are related to common families of thermoelectrics, such as Bi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 205 publications
(341 reference statements)
2
32
0
Order By: Relevance
“…The positive S for all samples confirms that holes are the dominant mobile charge carriers in these films, as expected 23,24,25 . The Seebeck coefficient monotonously increases with strain (from compressive to tensile) in agreement with the decrease of the electrical conductivity 24,50 , by almost a factor two from 127 V K -1 (compressive) to 208 V K -1 (tensile), consistently with other observations made on various thermoelectric materials under highpressures (S decreasing with pressure) 49 . It is worth noting that the Seebeck coefficients of the almost relaxed LSCO film on LSAT (160 V K -1 ) and another moderately tensile on STO substrate (180 V K -1 , see Supporting Information, Fig.…”
Section: Resultssupporting
confidence: 89%
“…The positive S for all samples confirms that holes are the dominant mobile charge carriers in these films, as expected 23,24,25 . The Seebeck coefficient monotonously increases with strain (from compressive to tensile) in agreement with the decrease of the electrical conductivity 24,50 , by almost a factor two from 127 V K -1 (compressive) to 208 V K -1 (tensile), consistently with other observations made on various thermoelectric materials under highpressures (S decreasing with pressure) 49 . It is worth noting that the Seebeck coefficients of the almost relaxed LSCO film on LSAT (160 V K -1 ) and another moderately tensile on STO substrate (180 V K -1 , see Supporting Information, Fig.…”
Section: Resultssupporting
confidence: 89%
“…Moreover, recent studies in thermoelectric materials show that Seebeck coefficients can increase with increasing pressures and temperatures (Chen et al. 2019; Morozova, Korobeinikov & Ovsyannikov 2019; Yoshino et al. 2020).…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] These materials are narrow bandgap semiconductors and typical thermoelectrics and the effect of high pressures could increase their Seebeck coefficient. [ 13 ] However, phases formed at high pressures and room temperature, are unstable at normal conditions: their recovered high‐pressure crystalline structure returns to the initial, rhombohedral ( R 3false¯ m ) structure.…”
Section: Introductionmentioning
confidence: 99%
“…[12] These materials are narrow bandgap semiconductors and typical thermoelectrics and the effect of high pressures could increase their Seebeck coefficient. [13] However, phases formed at high pressures and room temperature, are unstable at normal conditions: their recovered high-pressure crystalline structure returns to the initial, rhombohedral (R 3m) structure.Very little is known about metastable phases of sesquichalcogenides of elements of the bismuth subgroup, obtained after high-pressure-high-temperature (HPHT) treatment and retained under ambient conditions. Earlier Vereschagin et al [14] found an irreversible polymorphic transition at 6.5-12 GPa and 1075 K in Bi 2 Se 3 .…”
mentioning
confidence: 99%